AL-QUR’AN SEBAGAI SUMBER KONSEP PENDIDIKAN DALAM UPAYA MENGEMBANGKAN KEMAMPUAN INTI MANUSIA (DITINJAU DARI PERSPEKTIF FAZLUR RAHMAN) - Rahmy Febriani Ritonga; Asmila Damayanti; Luthfi Azima Harahap (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2025)
This article discusses the role of the Qur'an as a primary source in developing educational concepts aimed at enhancing the core abilities of humans, with a focus on Fazlur Rahman's thought. Using a literature review method, this research analyzes how the Qur'an provides normative foundations and inspiration for Islamic education, as well as how Rahman offers a systematic approach to interpreting the verses of the Qur'an. By exploring the moral and social values embedded in the Qur'an, this article highlights the importance of integrating religious knowledge and general knowledge in education. The findings indicate that a comprehensive understanding of the Qur'an can shape individuals who are not only intellectually capable but also possess strong character and ethics. This article aims to contribute to the reform of Islamic education to create a generation that is prepared to face the challenges of the times and positively contribute to society.